(The) DMZ: Dividing the Two Koreas - Koehler, Robert (Korea Essentials ;)
Four kilometers wide and stretching 250 kilometers from the East Sea to the West Sea, the Korean Demilitarized Zone divides the Korean Peninsula roughly in half, with the Republic of Korea to the south and the Democratic People's Republic of Korea to the north. Born of the fratricidal Korean War, it is perhaps the oldest continuous symbol of the Cold War and a tense border separating the two halves of the world's last divided nation, where democracy and communism still glare at one another in mutual animosity. Nowhere is this more evident than at the Joint Security Area (JSA) near the so-called "truce village" of Panmunjeom, where South Korean and North Korean soldiers stand practically face to face, the hostility almost palpable.